EXPERIMENTAL INVESTIGATION ON CONTROLLING PARAMETERS OF FLOWSLIDE FROM MSITURE CONTENT MEASUREMENTS - HAKRO, MUHAMMAD REHAN (2015)
In tropical areas, most cases of slope failures have been due to rainfall. Slope failure is one of the major geohazards that occur worldwide, including Malaysia. Due to rainfall, the moisture content increases gradually, and with the increase in moisture content, the negative pore pressure (matric suction) decreases. After soil saturation, the positive pore pressure increases, which in turn, decreases the effective stress and reduces the shear strength of soil. After the initiation of slope failure, in some cases, the movement of soil mass ceases quickly, while in other cases, the soil mass suffers from flowslide type of failure. The flowslide is also a type of slope failure, i.e., having large deformations and long run out distances, as well as receiving dozens of fatal accidents and economic losses. Therefore, identifying the parameters that control the initiation of flowslide would help in formulating mitigation measures.